2020
DOI: 10.1186/s12987-020-00186-4
|View full text |Cite
|
Sign up to set email alerts
|

Laminin 221 fragment is suitable for the differentiation of human induced pluripotent stem cells into brain microvascular endothelial-like cells with robust barrier integrity

Abstract: Background: In vitro blood-brain barrier (BBB) models using human induced pluripotent stem (iPS) cell-derived brain microvascular endothelial-like cells (iBMELCs) have been developed to predict the BBB permeability of drug candidates. For the differentiation of iBMELCs, Matrigel, which is a gelatinous protein mixture, is often used as a coating substrate. However, the components of Matrigel can vary among lots, as it is obtained from mouse sarcoma cells with the use of special technics and also contains variou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 22 publications
(27 reference statements)
0
23
1
Order By: Relevance
“…The present model presents improved tightness of the cell monolayer in comparison to cell line models such as hCMEC/D3, which displays low TEER values (~40 Ω·cm 2 , [ 3 ]) and for which an evaluation of the transcytosis of macromolecules across the model may only be carried using the so-called pulse-chase assay [ 105 ]. On the other hand, iPSC-derived BBB models have reported high TEER values (up to 2500 Ω·cm 2 , [ 106 ]), close to the ones reported in a physiological human BBB (~5000 Ω·cm 2 , [ 107 ]), however their differentiation conditions need to be carefully controlled to avoid an epithelial rather than endothelial phenotype [ 108 , 109 ]. In addition, no report can be found demonstrating transcytosis of anti-TfR antibodies in iPSC-derived BBB models, and comparable permeabilities for transferrin vs. human IgG have been shown [ 110 ].…”
Section: Discussionmentioning
confidence: 99%
“…The present model presents improved tightness of the cell monolayer in comparison to cell line models such as hCMEC/D3, which displays low TEER values (~40 Ω·cm 2 , [ 3 ]) and for which an evaluation of the transcytosis of macromolecules across the model may only be carried using the so-called pulse-chase assay [ 105 ]. On the other hand, iPSC-derived BBB models have reported high TEER values (up to 2500 Ω·cm 2 , [ 106 ]), close to the ones reported in a physiological human BBB (~5000 Ω·cm 2 , [ 107 ]), however their differentiation conditions need to be carefully controlled to avoid an epithelial rather than endothelial phenotype [ 108 , 109 ]. In addition, no report can be found demonstrating transcytosis of anti-TfR antibodies in iPSC-derived BBB models, and comparable permeabilities for transferrin vs. human IgG have been shown [ 110 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the use of laminin isoforms during the differentiation of iBMECs has been studied, suggesting laminin 221 (LN 221) as an enhancer of iBMEC barrier properties, but this study did not evaluate the effect of laminin isoforms of the endothelial BM on the culture of differentiated iBMECs [26]. Another study reported the effect of different ECM proteins including laminin on TEER of differentiated iBMECs; however, specific laminin isoforms of the endothelial BM were not investigated [27].…”
mentioning
confidence: 97%
“…The recognized lot-to-lot variability in Matrigel ® composition has led researchers to examine specific components of ECM to generate a more controlled and reproducible environment with less lot-to-lot variation. A recent study compared defined coatings to Matrigel ® for the differentiation of iPSC-derived BMECs [ 279 ] and found that cells cultured on laminin-221 had superior barriers, with higher TEER values, and the barrier was maintained for longer. Though laminin-221 is slightly different from the laminin-211 secreted by astrocytes, they both share the alpha-2 chain, which is suggested to be the main regulator of the maturation and function of the BBB [ 107 ].…”
Section: Decision Workflow: Factors To Consider When Selecting a Model Systemmentioning
confidence: 99%